Unified blended learning environment: the Kazakhstani context - S. M. Bakhisheva; E. V. Tikhonyuk; Z. G. Mukhtar; R. S. Kinzhekova; A. M. Kemeshova (Образование и наука)
Introduction. The present work investigates the issues related to technological and administrative support for the blended learning process in higher education in Kazakhstan.Aim. This article aims to develop an author’s conceptual model of a unified system for managing the blended learning process by defining the evaluation criteria for an optimal educational environment.Methodology and research methods. The research was conducted in four stages using mixed methods. The first stage involved conducting surveys with participants in the educational process to identify the challenges they encountered while working in a digital educational environment and explore potential solutions. The second stage involved developing evaluation criteria for an optimal educational environment for blended learning. The third stage entailed empirical testing of existing educational platforms that are utilised by 33 leading Kazakh universities. The fourth stage witnessed the development of a pilot conceptual model for a unified environment for blended learning.Results. Based on the integration of Learning Activity Management System (LAMS), Learning Management System (LMS), and Education Content Management System (ECMS), a conceptual model of a unified environment for blended learning was developed. The criteria for the optimal educational environment of blended learning were developed to evaluate the technical, functional, and didactic capabilities of educational platforms.Scientific novelty. The study resulted in the development of a conceptual model for a unified environment for managing the blended learning process.Practical significance. The proposed model can be employed by the administrations of top Kazakhstani universities to implement a student-centred approach to the educational process.